The excess electron in polymer nanocomposites. Issue 43 (29th October 2018) - Saiz, Fernan; Quirke, Nick
Abstract : We have used ab initio molecular dynamics and density-functional theory (DFT) calculations at the B3LYP/6-31G** level of theory to evaluate the energy and localisation of excess electrons at a number of representative interfaces of polymer nanocomposites. Abstract : We have used ab initio molecular dynamics and density-functional theory (DFT) calculations at the B3LYP/6-31G** level of theory to evaluate the energy and localisation of excess electrons at a number of representative interfaces of polymer nanocomposites. These modelled interfaces are made by combining liquid water and amorphous slabs of polyethylene and silica. The walls of the amorphous silica slabs are built with two surface chemistries: Q 4 or fully-dehydroxylated and Q 3 /Q 4 or partially-hydroxylated with a silanol content between 1.62 and 6.86 groups per nm 2 . Our results indicate that in silica/polyethylene systems an excess electron would sit at the interface with energies between −1.75 eV with no hydroxylation and −0.99 eV with the highest silanol content. However, in the presence of a free water film, the chemistry of the silica surface has a negligible influence on the behaviour of the excess electron. The electron sits preferentially at the water/vapour interface with an energy of minus a few tenths of an eV. We conclude that the moisture content in a wet polymer nanocomposite has a profound influence on the electron trapping behaviour as it produces much lower trapping energies and a higher excess-electron mobility compared to the dry material.